Communityserviceforinfantswithcleftlipand palate at Mitra Sejati andGrandmed Hospital North Sumatera - Syafrinani, Syafrinani; Chairunnisa, Ricca; Rusdy, Hendry (Indonesian Journal of Prosthodontic, 2021)
Cases of cleft lip and palate (CLP) in infants were many in Medan and surrounding areas.There were about 150 cases of infants with CLP in a year handled by Mitra Sejati Medan Hospital andGrandmed HospitalLubuk Pakan,butthetreatmentgiven was only surgical treatment,while the follow-up care,which isthefabricationofartificialpa-late or feeding plate before or after surgery,cannot be facilitated.Until now CLP further treatment cannot be done becausetheparentsdonotknowthetreatmentand most of them came from groups with low socio-economic level andthefabricationof feedingplaterequiredhigh costs.To overcome this problem,we held communityserviceby fabricating feeding plates as feeding aids for babies with CLP.The method used to achieve this goalofserviceis collectingdatafrompatientswithCLPinthetwohospitals,generalexaminationbypediatrician,makingtheimpression of the oral cavity to create the working cast,making outline design,doing thewaxpatternandfeeding plate fabrica-tioninthe laboratory using hard and soft acrylic materials combination.The insertion of feedingplatesisperformed at the hospital and evaluated whether the baby can drink milk normally using a bottle. Body weight changes are evaluated every month until the baby is declared ready for surgery.